Legal Protection of Indonesian Migrant Workers Abroad: A Review of Law No. 18 of 2017 - Divani Tsamara Madiyya; Kesya Putri Kuswara (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the migration of Indonesian workers constitutes an important phenomenon in the global economic context, providing strategic contributions through remittances and the improvement of family welfare. However, in reality, although national regulations have evolved to protect the rights of Indonesian Migrant Workers (PMI), conditions in the field still reveal significant structural vulnerabilities, including contract violations, exploitation, limited access to legal remedies, and minimal post-placement assistance. These conditions underscore the need for a comprehensive, integrated, and sustainable protection system to ensure that migrant workers can work safely, with dignity, and with their rights fully protected. This study aims to analyze the forms of legal protection for Indonesian Migrant Workers abroad based on Law Number 18 of 2017, identify challenges in its implementation, and evaluate government strategies in strengthening the protection system for PMI. This article employs a normative legal research approach, using library research as the primary data collection method, complemented by descriptive-analytical analysis of legislation, legal literature, and relevant case studies. The results indicate that a protection framework based on the migration cycle, the integration of legal, social, and economic aspects, as well as the active roles of central and local governments, diplomatic representatives, and local communities, are key to the successful protection of Indonesian Migrant Workers.